CORPORATE GOVERNANCE DAN PENGUNGKAPAN PENGENDALIAN INTERN - Zulfikar, Rudi; Rosiana, Rita; Naisah, Ratu Ayu (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2015)
The purpose of this research is to examine the role of Corporate Governance practice to internal control disclosure in Indonesian banking industry. Corporate Governance practice (CG) is measured by proportion independent member in Board of Directors, the proportion of Board of Directors independent, managerial ownership, institusional ownership, audit committee size, eduaction background members of audit committee. The sample of this study is 87 banks listed  in the Indonesian Stock Exchange within the year of 2010 and 2012. The data are drawn from the annual report,  multiplregresion is used to analyze the data.   This research find, that Board of Directors size,  institusional ownership and eduaction background members of audit committee are significant factors to internal control  disclosure. Keywords : corporate governance, internal control disclosure